Improving supply chain resilience at tetra pak using multi-stage supply chain - Hiu, Elsa Man Leung (2014)
Due to the global expansion of Tetra Pak’s supply chain network, it is becoming more vulnerable to many disruptions. These disruptions often incur additional costs, require time to respond and recover. The base paper supply was identified as the most vulnerable area of the Tetra Pak Jurong and Asia Clusters’ supply chain; and a multi-stage supply chain was proposed to improve the supply chain’s resilience. A statistical model was constructed to select the optimal location of the central warehouse for the proposed multi-stage supply chain. After evaluating the resilience to disruptions and the cost effectiveness of potential supply chain designs, the multi-stage supply chain with central warehouse in Yantian, China was found to be overall most resilient and cost effective among all the supply chains. It also incurs a lower additional cost to recover in the event of a disruption such as changes demand forecast accuracy, demand surges and shipping disruptions. As a result, establishing this multi-stage supply chain is recommended.